Combination Effect of Antituberculosis Drugs and Ethanolic Extract of Selected Medicinal Plants against Multi-Drug Resistant Mycobacterium tuberculosis Isolates - Prabasiwi Nur Fauziyah; Elin Yulinah Sukandar; Dhyan Kusuma Ayuningtyas (MDPI AG, 2017)
Adverse drug reaction and resistance to antituberculosis drugs remain the causes of tuberculosis therapeutic failure. This research aimed to find the combination effect of standard antituberculosis drugs with Hibiscus sabdariffa L., Kaempferia galanga L., and Piper crocatum N.E. Br against multi-drug resistant (MDR) Mycobacterium tuberculosis isolates. Two MDR strains (i.e., isoniazid/ethambutol resistant and rifampicin/streptomycin resistant) of M. tuberculosis were inoculated in Löwenstein-Jensen medium containing a combination of standard antituberculosis drugs and ethanolic extracts of H. sabdariffa calyces, K. galanga rhizomes, and P. crocatum leaves using various concentration combinations of drug and extract. The colony numbers were observed for 8 weeks. The effect of the combination was analyzed using the proportion method which was calculated by the mean percentage of inhibition reduction in a number of colonies on drug-extract containing medium compared to extract-free control medium. The results showed that all three plant extracts achieved good combination effects with rifampicin against the rifampicin/streptomycin resistant strain. Antagonistic effects were, however, observed with streptomycin, ethambutol and isoniazid, therefore calling for caution when using these plants in combination with antituberculosis treatment.